Implementation of Technology in Cross-Cultural Counseling Process: Challenges and Opportunities - Hapipi, Muh.; Ahmad, Khatib Romli; Amir, Lalu Sibuan (International Journal of Multicultural Counseling and Development, 2024)
Abstract. This study aims to investigate the impact of technology on the development of cross-cultural competence and enhance cross-cultural communication effectiveness in the context of counseling. The research adopts a Systematic Literature Review approach, utilizing sources indexed in Google Scholar, DOAJ, and Scopus, with publications selected from 2013 to 2024. The evaluation of the research indicates that the implementation of cross-cultural counseling is significantly influenced by the availability of technological infrastructure. Despite technology providing ease of access, technical challenges such as limited written communication skills and unfamiliarity with technology need to be addressed to maximize counseling effectiveness. The security and privacy aspects of implementing technology in cross-cultural counseling are complex issues that require special attention, including adjustments based on client preferences regarding anonymity and personal connection. The objective of this study is to gain a profound understanding of the challenges and opportunities in integrating technology into the cross-cultural counseling process, with a focus on improving communication skills, addressing technical constraints, and implementing policies and security practices to ensure the successful implementation of technology in the cross-cultural counseling context.